Pengembangan Media Pembelajaran Menggunakan Geogebra Classroom pada Materi Limas - Lismareni, Neni; Adiansyah, Marta; Widiawati, Widiawati (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to develop a valid and practical learning media product using GeoGebra for pyramids in the seventh grade of Muhammadiyah Pagaralam Junior High School in the 2024/2025 academic year. This research is a research and development (R&D) project involving 32 seventh grade students of Muhammadiyah Pagaralam Junior High School. The development model used was ADDIE (Analysis, Design, Development, Implementation, Evaluation). The product developed in this study was declared valid based on validation by media experts, material experts, and language experts, with percentages of 86%, 78%, and 89%, respectively. The learning media was categorized as very feasible, feasible, and very feasible, respectively. The results of the student response questionnaire trial showed that the first one-to-one stage achieved practical criteria, the second small group stage achieved very practical criteria, and the final field test stage achieved very practical criteria. Therefore, the learning media using GeoGebra Classroom is considered valid and practical.   Keywords: Development, Learning Media, GeoGebra Classroom, Pyramids